Revisiting the Protestant Ethic and the Spirit of Capitalism: Understanding the Relationship between Ethics and Enterprise - Carr, Patricia (Journal of business ethics, 2003)
The last twenty years have been characterised by a significant shift inattitudes towards enterprise, entrepreneurship and small business.However though valued, entrepreneurs and small businesses are underincreasing pressure to be mindful of the social and moral implicationsof their activities. These developments have given the question ofbusiness ethics a central place in organisational research. Much of thisattention has been directed at the large organisation, despite the factthat the majority of businesses are small firms., A significant amount of the research in the area of business ethicsis prescriptive in orientation with an underlying assumption thatenterprise and ethics are mutually exclusive, with a key aim being tobring them together. In looking at the question of ethics and enterprise(understood here as small business activity) this paper will argue thata prescriptive approach should be avoided and an alternative will beoutlined. With reference to the concept of Lebensfuhrung,translated in Weber's The Protestant Ethic and the Spirit ofCapitalism as the "manner of leading one's life", this paper willargue that rather than conceiving of enterprise as an activity whichneeds an infusion of ethics, enterprise is by its very nature ethical.It is ethical in the sense of advocating a particular way by which oneshould live one's life or in the case of small business owners,presenting an account of how a small business should be owned, nurturedand developed.